توثيــق إجراءات الفحص الضريبي من منظور متطلبات إدارة الجودة الشاملـة دراسة تطبيقية على دائرة ضريبة الدخل والمبيعات في وزارة المالية في الأردن (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن لإدارة الجودة الشاملة العديد من المتطلبات ومن أهمها تحديد وتوثيق الإجراءات والعمليات المتعددة التي تؤثر في جودة المنتج أو الخدمة، لذلك قامت دائرة ضريبة الدخل والمبيعات في الأردن لدى اعتمادها نظام الجودة بتحديد إجراءات كل خدمة من الخدمات المساندة وتوثيقها، مما أدى إلى زيادة  كفاءة أدائها وفعاليتها وسرعة إنجازها ودقته باستثناء خدمة الفحص الضريبي التي تشكل النسبة الأكبر والأهم من عمل الدائرة، والذي لا يزال يتم على نحو غير مؤسسي, وغير متجانس في أداء الفاحصين واتساع مساحة اجتهادهم في تقدير الربح الخاضع للضريبة، إضافة لازدياد حالات التهرب الضريبي، الأمر الذي استرعى اهتمام الباحث في محاولةٍ منه لإبراز دور الفحص الضريبي وأهميته من جهة, وتحديد إجراءات عمله وتوثيقها من جهة أخرى، بهدف مساعدة الإدارة الضريبية على إخضاعه لنظام إدارة الجودة الشاملة مستقبلاً. There are needs and requirements for the comprehensive quality system: one of these important requirements is to define and document the different procedures and operations which affect product quality and services. So the Income and Sale Department in Jordan accepts quality system in order to define and document procedures for each supplementary service, which lead to increasing effectiveness and efficacy of work and accuracy of doing works except taxation check services which represent the high percent and most important work of the Department's jobs. It is still done without institutional steps for inspector works and the big area to predict and calculate the tax income. This is in addition to the increase of getting away from tax payment. So, the researcher tries to magnify the importance of the role of taxation check from one side and define and document procedures for the other side in order to help the taxation management to make comprehensive quality management in the future.